Upaya Efisiensi dan Peningkatan Ketersediaan Nitrogen dalam Tanah pada Tanaman Bawang Merah (Allium ascalonicum L) melalui Pemberian Mikoriza Arbuskular - Murni, Widya Sari; Purnamayani, Rima (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Murni WS, Purnamayani R. 2019. Efficiency efforts and Increasing availability of nitrogen in soil on shallot (Allium ascalonicum L) through arbuscular mycorrhiza. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 186-191. Palembang: Unsri Press. Nitrogen is a macro nutrient that is very important in increasing plant growth and yield. Only 30-50% of N fertilizer from anorganic fertilizer that can be absorbed by plants. Shallow rooting in shallots causes inefficient absorption of nutrients from the soil both from organic matter and anorganic fertilizers. The efficiency of nutrient absorption is greater in mycorrhiza plants compared to plants that have no mycorrhiza, because of the presence and active transport of hyphae found in the symbiotic structure between mycorrhizal fungi and plant roots. The purpose of this paper is to provide information on efforts to improve the efficiency and availability of Nitrogen in the soil in shallot (Allium ascalaonicum L) through arbuscular mycorrhiza. Mycorrhizal fungi in plant roots have the ability to absorb N from organic matter in the soil. Mycorrhizal fungal hyphae can intensify other N fixing bacteria to provide N sources in the soil. Mycorrhizal fungi reduce N nutrient losses through mineralization by abundant N-fixing bacteria due to improved soil structure by mycorrhizal fungi. This is due to external hyphae of mycorrhizal fungi that provide C as an energy source of fastening bacteria N. Compatibility of mycorrhizal fungi with red onion plants allows the roots to expand absorption of nutrients by the roots so that it is expected to reduce the input of anorganic fertilizers without reducing crop yields.Keywords: arbuscular mycorrhiza, efficiency, nitrogen availability, shallots